A study of the heat transfer in hydrogen fueled internal combustion engine - Khalaf Ibrahim, Hamada (2012)
Heat transfer in the internal-combustion engine is a crucial phenomenon because of it affects the engine performance, efficiency and emissions. The aim of this thesis is to characterize the time-averaged heat-transfer and instantaneous heat-transfer of the direct-injection hydrogen-fueled engine. A one-dimensional model was developed based on the gas dynamic and heat-transfer concepts for characterizing the time-averaged heat-transfer. This model was developed using the real engine specifications with the capabilities of GT-POWER software. The dimensionless analysis for TAHT was performed based on the output results from one-dimensional model. The multidimensional model based on the finite volume approach for characterizing the instantaneous heat-transfer. The structural three-dimensional model was constructed and then discretized using the structured hexahedron mesh. The governing equations for reactive flow with the accompanied physical phenomena were solved numerically. A novel subroutine was integrated to simulate the hydrogen-injection process. Simplified single-step mechanism was considered for estimating the reaction rate of hydrogen oxidation. The modified wall-function was used for resolving the near wall transport. Arbitrary Lagrangian-Eulerian algorithm was adopted for solving the governing equations. Whereas the sub-models were solved utilizing the operator splitting approach, then it was incorporated with the main program. The influences of the engine speed, equivalence ratio and start of injection timing were investigated. Experimental study shows that the time-averaged heat-transfer and instantaneous heat-transfer models are adequately accurate. The equivalence ratio and engine speed were observed to have significant impacts on characteristics of the time-averaged heat-transfer as well as instantaneous heat transfer. It was demonstrated that ignoring the impact of the equivalence ratio on the time-averaged heat-transfer is unjustifiable, especially on the heat-transfer correlation. Accordingly, the equivalence ratio was established in a new correlation form of the time-averaged heat-transfer. The reliability of the newly developed correlation was verified using the Taylor's correlation. The relative error was reduced from 70 % to around 10 %. Thermal field analysis was used for demonstrating the trends of the instantaneous heat transfer. It was observed that there is a crucial distinction between the lean and ultra-lean mixture as well as the engine speed. Furthermore, a non-uniform behavior was found for the impact of the equivalence ratio on the temperature distributions. Moreover, the heat release rate, instantaneous rate of heat loss, cumulative heat loss and heat transfer coefficient were used for monitoring the behaviour of the instantaneous heat transfer. The instantaneous heat transfer parameters were increased around 35% when increasing the equivalence ratio within the range of the finest operation while these parameters are acquired within 10% increase for the entire engine speed range. It can be comprehended that the developed models are powerful tools for estimating the heat transfer of hydrogen-fueled engine. The developed predictive correlation is highly recommended for predicting the heat transfer of hydrogen-fueled engine.